O7C.2 Developing a measuring strategy for monitoring and evaluation of a national occupational health intervention programme in great britain (GB). (April 2019) - Chen, Yiqun; Curran, Andrew
Abstract : The Health and Safety Executive (HSE) is the GB regulator for health and safety at work. The HSE Health and Work (H&W) program designs and carries out a wide range of interventions; including inspection, enforcement and other regulatory activities as well as prevention; targeting priority health conditions in high-risk sectors. It is anticipated that long-term, sustainable and coordinated actions developed as part of the program will over time improve awareness, behaviors, control of exposures, and, as a result, prevent work-related ill health in GB workforce. An HSE Measuring Strategy, together with measurement framework and principles, has been developed. The measurement framework draws together data systems, covering Attitudes (A), Behaviors (B), Control of exposures (C), and Disease and work-related ill health reduction (D), based on a simple model to provide evidence required for evaluating the short, medium and long term impacts of the large scale and complex H&W program on the GB health and safety system. The Strategy gives a new focus on measuring behavioral changes and risk reductions; and emphasizes longitudinal measurement designs to assess progress over time. For developing the Strategy, workshops were organized to bring stakeholders across HSE to review existing systems for conducting population surveys, collecting exposure intelligence and occupational health surveillance, which have contributed to forming a long-term vision of fit-for-purpose measurement systems. We will present the development of the Strategy and the plans to implement it with the H&W program, which requires close collaborations between epidemiologists and social researchers, policy makers, and other multidisciplinary regulatory specialists. The lessons learnt will help HSE towards building the right evidence base for monitoring and evaluation of a range of national level intervention programs for work-related ill health prevention. ©British Crown copyright (2019)